Pengaruh Intellectual Capital, Capital Structure Terhadap Firm Performance dengan Good Corporate Governance Sebagai Variabel Moderator - Novyarni, Nelli; Rizkha Fadhilah; Harni, Reni; Krisnando (Jurnal EMT KITA, 2024)
Many companies have not met their performance targets over the past year, indicating poor performance. This study aims to analyze whether good corporate governance can moderate the influence of intellectual capital and capital structure on company performance. The sample consisted of 80 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The methodology used was multiple linear regression analysis, with the assistance of EViews 12 software. The study found that intellectual capital and capital structure do not affect company performance, but good corporate governance can moderate the effect of intellectual capital and capital structure on company performance. The conclusion of this study is that good corporate governance can moderate the influence of intellectual capital and capital structure on company performance.